Cost-effectiveness analysis of a single-inhaler triple therapy for patients with advanced chronic obstructive pulmonary disease (COPD) using the FULFIL trial: A UK perspective. (2019) - Schroeder, Melanie; Shah, Dhvani; Risebrough, Nancy; Martin, Alan; Zhang, Shiyuan; Ndirangu, Kerigo; Briggs, Andrew; Ismaila, Afisi S.
Abstract: Objectives: The clinical benefit of once-daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) versus twice-daily budesonide/formoterol (BUD/FOR) for patients with symptomatic chronic obstructive pulmonary disease (COPD) was demonstrated in a clinical trial setting (FULFIL [NCT02345161]). The lifetime cost-effectiveness analysis of FF/UMEC/VI versus BUD/FOR, based on FULFIL data, is reported here. Methods: A previously developed and validated GALAXY-COPD linked-risk equation model was used to assess the cost-effectiveness of FF/UMEC/VI from the UK National Health Service (NHS) perspective. Baseline characteristics and efficacy results from FULFIL and UK NHS reference cost data (2017) were included as inputs. Exacerbation rates (undiscounted), costs, life years (LYs; undiscounted) and quality-adjusted life years (QALYs), and the incremental cost-effectiveness ratio (ICER) were calculated over a lifetime horizon. Costs and QALYs were discounted at 3.5% per year, beyond one year, in accordance with National Institute for Health and Care Excellence (NICE) guidelines. Deterministic and probabilistic sensitivity analyses were performed to evaluate the robustness of the results. Results: Predicted cumulative exacerbations per patient over a lifetime were 8.393 with FF/UMEC/VI and 10.456 with BUD/FOR. Patients receiving FF/UMEC/VI gained an additional 0.764 LYs and 0.492 QALYs, at an additional mean cost of £1, 652, resulting in an ICER of £3, 357 per QALY gained (95% confidence interval: £1, 816, £5, 194) compared with BUD/FOR. The ICER remained below £6, 000 in all but one of the scenario and sensitivity analyses. Conclusions: Compared with BUD/FOR, treatment with FF/UMEC/VI was predicted to improve health outcomes at an additional cost that suggests it would be cost-effective for patients with COPD in the UK. Highlights: FF/UMEC/VI was predicted to reduce moderate/severe exacerbation rates vs BUD/FOR. FF/UMEC/VI was predicted to improve quality-adjusted survival vs BUD/FOR. FF/UMEC/VI was cost-effective vs BUD/FOR in UK NHS patients with symptomatic COPD. In all scenario and sensitivity analyses, FF/UMEC/VI remained cost-effective.